Did The Program Kampung Iklim Lead Farmers to Implement more Adaptation Strategies? Case Study of Rice Farmers in Sleman Regency - Moh. Wahyudi Priyanto; Jangkung Handoyo Mulyo; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2020)
The negative impacts of climate change caused many losses for farmers. One solution to minimize losses is to implement a climate change adaptation strategy. The Indonesian government established a program called the Program Kampung Iklim/Proklim in 2012 which aims to increase awareness of climate change and the capacity to implement community adaptation strategies. This study aimed to determine the effect of the Proklim on the implementation of climate change adaptation strategy by farmers. The study was conducted in Proklim and non-Proklim locations. By implementing the simple random sampling method, it was obtained 112 samples divided into 56 farmers from each Proklim and non-Proklim location. The results showed that farming experience, land area, membership in farmers group, access to weather information, awareness towards climate change and perceptions towards climate change risks are associated with more practice of adaptation strategy. The results also showed that the implementation of adaptation strategy was influenced by the Proklim location, so that the farmers involved in the program locations applied more climate change adaptation strategy than the farmers in non-program locations. The authors recommend that Proklim needs to be applied in many locations, especially areas that are vulnerable to climate change, so farmers can improve the implementation of climate change adaptation strategies.